EXAMINING STUDENTS’ ORAL CORRECTIVE FEEDBACK PREFERENCES FOR IMPROVING SPEAKING PROFICIENCY - Nurjanah, Lailatul; Rahmaningtyas, Hasti; Yaniafari, Rahmati Putri (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2024)
This article examined the fundamental OFC types that students prefer for oral corrective feedback to improve their speaking ability in speaking class. It aims to give a clearer understanding of beliefs alignment between teachers and students, thus enabling them to choose appropriate OCF techniques that will enhance students’ performance. This study also contributes to the comprehension of OCF use in the educational context of Indonesia which is aimed at evidencing data-based learning. This research was carried out at Universitas Negeri Malang specifically in the Department of English and used descriptive quantitative design through surveys where respondents were 116. The instrument of this study was a questionnaire. The result indicates that when providing OCF, student emotions and preferences should be considered since these directly affect both the kind of feedback to be given and its effectiveness. In terms of the “delivery” of the feedback, students prefer metalinguistic and recast feedback types. However, there are some discrepancies in terms of their perceived effectiveness among students. Notably, metalinguistic, repetition, as well as recast OCF types, proved most advantageous concerning proficiency development. Furthermore, indirect OCF is more favored than direct administration timing. This research implies that metalinguistic, repetition, and recast feedback are types of OCF that are suitable for use in speaking classes with the aim of improving speaking performance. Since this research has not provided a data-based explanation of how students' preferred OCF helps improve their performance, future research is expected to conduct an in-depth exploration of its successful use.